Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Florida)--Long-spined black sea urchin - Ogden, John C.; Carpenter, Robert C. (Washington, D.C. U.S. Department of the Interior, 1987)
U.S. Fish. Wildl. Serv. Biol. Rep. 82(11.77)
Keywords: Invertebrates; Fishes; History; Long spined black sea urchin-South Florida